The relationship between hope and patient activation in consumers with schizophrenia: Results from longitudinal analyses. Issue 3 (30th August 2015) - Oles, Sylwia K.; Fukui, Sadaaki; Rand, Kevin L.; Salyers, Michelle P.
Abstract: Hope (goal-directed thinking) and patient activation (knowledge and skills to manage one's illness) are both important in managing chronic conditions like schizophrenia. The relationship between hope and patient activation has not been clearly defined. However, hope may be viewed as a foundational, motivating factor that can lead to greater involvement in care and feelings of efficacy. The purpose of the present study was to understand the prospective relationship between hope and patient activation in a sample of adults with schizophrenia ( N =118). This study was a secondary data analysis from a study on Illness Management and Recovery (IMR) – a curriculum-based approach to schizophrenia self-management. Data were collected at baseline (prior to any intervention), and at 9 and 18-month follow-up. As predicted, hope and patient activation were significantly related with each other, showing large positive concurrent correlations. Demographics and background characteristics were not significantly related to patient activation or hope. Longitudinal analyses found no specific directional effect, yet suggested that hope and patient activation mutually influence each other over time. Our findings add flexibility in designing recovery-based interventions – fostering hope may not be a pre-requisite for activating consumers to be more involved in their own care. Highlights: Hope and patient activation were positively correlated at each time period. Longitudinal analyses found no specific directional effect. Both constructs predicted the future status of consumers. The influence of hope and patient activation was reciprocal and consistent over time.